A New Imaginary Term in the Second-Order Nonlinear Susceptibility from Charged Interfaces - Ma, Emily; Ohno, Paul E; Kim, Jeongmin; Liu, Yangdongling; Lozier, Emilie H; Miller, Thomas F; Wang, Hong-Fei; Geiger, Franz M (The journal of physical chemistry letters, 2021)
Nonresonant second harmonic generation (SHG) phase and amplitude measurements obtained from the silica–water interface at varying pH values and an ionic strength of 0.5 M point to the existence of a nonlinear susceptibility term, which we call χX (3), that is associated with a 90° phase shift. Including this contribution in a model for the total effective second-order nonlinear susceptibility produces reasonable point estimates for interfacial potentials and second-order nonlinear susceptibilities when χX (3) ≈ 1.5χwater (3). A model without this term and containing only traditional χ(2) and χ(3) terms cannot recapitulate the experimental data. The new model also provides a demonstrated utility for distinguishing apparent differences in the second-order nonlinear susceptibility when the electrolyte is NaCl versus MgSO4, pointing to the possibility of using heterodyne-detected SHG to investigate ion specificity in interfacial processes.